Transformative Effect: Rise of Intelligent Data Management in Integration with AI - Achanta, Padma Rama Divya (Transactions on Engineering and Computing Sciences, 2025)
Power of Artificial Intelligence (AI) is reshaping the way organizations collect, process and leverage data. Traditional data management systems often struggle to handle velocity, volume, and variety of modern data and types. This leads to inefficiencies in the system and losing opportunities of growth. AI powered data management systems handle these challenges very efficiently by automating tasks such as data cleansing, classification, integration to analysis. This transformative rise of intelligent data management, powered by Artificial Intelligence (AI) is reshaping the way organizations collect, process, and leverage data and has enabled organizations to extract actionable insights in real-time. This integration of AI combined with intelligent data management helps businesses to enhance its decision-making process, streamlines operations and unlocks new avenues of growth and innovation across the industries. This paper explores the transformative effects of intelligence data management systems powered by AI, highlighting its capabilities, benefits and potential pitfalls. Furthermore, it outlines its implications on privacy & ethical challenges which need to be addressed and future role of AI in shaping the future of data-driven ecosystems.